Quantum Entanglement in Multi-Particle Systems - Maxime Lambert; Olivier Lefevre; Dimitar Hristov (Journal of Tecnologia Quantica, 2025)
The background of this research focuses on the phenomenon of quantum entanglement in multi-particle systems involving photons and atoms. Although much research has been done on entanglement in two-particle systems, challenges arise when the system is expanded to include more particles. This study aims to explore how entanglement is maintained in multi-particle systems and to understand the differences between photons and atoms in this context. The method used is an experiment that involves measuring entanglement in a system of photons and atoms that are separated at a certain distance. The results showed that photons can maintain entanglement over very long distances (up to 1 kilometer), while atoms show a decrease in entanglement levels over longer distances, but can still be used in quantum computing applications at shorter distances. The study concluded that photons are more stable in maintaining entanglement over long distances, while atoms are more suitable for quantum computing applications in small systems. Further research is needed to address the limitations related to the stability of entanglement over longer distances and to develop applications in larger multi-particle systems.